Best Answer

6x3 - x2 + 17 = 2x2 + 47

6x3 - x2 - 2x2 = 47 - 17

x2(6x - 1 - 2) = 30

this is the simplest factorisation.

Q: How do you factor 6x3-x2 plus 17 equals 2x2 plus 47?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

2x2+13x+15 = (2x+3)(x+5)

2x2 + 11x + 15 = (x + 3)(2x + 5).

-7

No.

Related questions

2x2 equals 5

3

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

2x2+13x+15 = (2x+3)(x+5)

2x2 + 11x + 15 = (x + 3)(2x + 5).

8 - 2x2 = x + 22 - 7Combine like terms on the right side:8 - 2x2 = x + 15Subtract 8 from each side:-2x2 = x + 7Add 2x2 to each side:0 = 2x2 + x + 7

-7

4x4 + 1 = (2x2 - 2x + 1)(2x2 + 2x + 1)

x2 + x2 = 2x2

No.

22 = 4

Doesn't factor evenly, use quadratic